Change gears before speeding up: The roles of Chief Executive Officer human capital and venture capitalist monitoring in Chief Executive Officer change before initial public offering. (22nd June 2020) - Chahine, Salim; Zhang, Yan (Anthea)
Abstract: Research Summary: With data on 1, 156 venture capitalist (VC)‐backed U.S. initial public offerings (IPOs), we find that the initial level of Chief Executive Officer (CEO) human capital (HC) when a firm receives its first VC investment is negatively related to the likelihood of changing CEO before IPO. The distance between a firm and its lead VC has a positive effect on the likelihood and this effect is stronger when the initial CEO HC is lower. These results suggest that as a larger distance amounts to greater cost of VC direct monitoring, VC is more compelled to change CEO, especially when initial CEO HC is lower. Controlling for the endogeneity of CEO change, we find that CEO change before IPO has a positive relationship with the firm's IPO valuation and changes in operating performance. Managerial Summary: Changing CEO prior to IPO is common in startups, especially in those backed by VCs. We argue that VC can monitor a portfolio firm in two ways (which are not mutually exclusive): directly monitoring onsite the firm and indirectly monitoring relying upon the firm's top management especially CEO. We propose and find empirical evidence to support that as a larger distance between a firm and its lead VC amounts to greater cost of direct monitoring and thus making direct monitoring less feasible, the VC is more compelled to change CEO, especially when the CEO is deemed less capable (i.e., having a lower level of human capital). We also find that CEO change before IPO increases a firm's IPO valuation and changes in operating performance.